STRATEGI MENGATASI KEKERASAN TERHADAP ANAK MELALUI PESANTREN RAMAH ANAK - Nurlaela, Nurlaela; A., Muh. Mujaddidi; Arifin, Syamsul (LPPM Institut Pendidikan Nusantara Global, 2023)
This article aims to find out strategies for overcoming violence against children through child-friendly Islamic boarding schools. This study was guided by a problem formulation, namely how to overcome violence against children through child-friendly Islamic boarding schools. This study is a literature review or often called a literature review. The analysis approach uses a content analysis approach. The author found that the strategy for overcoming violence against children through Child-Friendly Islamic Boarding Schools is: first, training of teaching staff; second, the establishment of a code of ethics and anti-violence policies; third, restorative approach; fourth, education on children's rights; fifth, the role of parents and family; sixth, carry out monitoring and evaluation; seventh, campaign and promotion of Child Friendly Islamic Boarding Schools; and eighth, leadership commitment. The results of this study contribute to strengthening the foundation for developing models and guidelines for Islamic boarding schools to become Child Friendly Islamic Boarding Schools.